Doing exercise psychology - Andersen, Mark B. 1951-; Hanrahan, Stephanie J. 1961- (Human Kinetics, 2015)
Addresses the challenging psychological components of physical activity. Bringing together a field of experts, this book features diverse topics, bridging health psychology and exercise psychology to demonstrate the increasingly important role of physical activity in overall wellness and health.